2022
DOI: 10.3390/bdcc6010003
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Political Polarization on Social Media by Deleting Bot Spamming

Abstract: Social media platforms are part of everyday life, allowing the interconnection of people around the world in large discussion groups relating to every topic, including important social or political issues. Therefore, social media have become a valuable source of information-rich data, commonly referred to as Social Big Data, effectively exploitable to study the behavior of people, their opinions, moods, interests and activities. However, these powerful communication platforms can be also used to manipulate con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
0
13
0
2
Order By: Relevance
“…Since social media platforms are key drivers of traffic towards far-right websites (together with search engines) ( Chen et al, 2022 ), it is important to note that many of the links towards such websites are made available to the public through bots. Although our findings may point to the automatic removal of bots from political debates as a possible intervention ( Cantini et al, 2022 ), there is evidence that attempts at moderating content can lead to even greater polarization ( Trujillo & Cresci, 2022 ), hence the need for caution when intervening.…”
Section: Discussionmentioning
confidence: 72%
“…Since social media platforms are key drivers of traffic towards far-right websites (together with search engines) ( Chen et al, 2022 ), it is important to note that many of the links towards such websites are made available to the public through bots. Although our findings may point to the automatic removal of bots from political debates as a possible intervention ( Cantini et al, 2022 ), there is evidence that attempts at moderating content can lead to even greater polarization ( Trujillo & Cresci, 2022 ), hence the need for caution when intervening.…”
Section: Discussionmentioning
confidence: 72%
“…Cantini et al manage to demonstrate the analytical value for electoral climates from social network data in an effective way, as long as they manage to clean from the interactions agents that muddy the discussion or manage to remove concepts that confuse the object of search: voting intention and information about electoral options. (Cantini et al, 2022). Skoric et al review predictive studies using social network data to predict elections and indicate that the highest accuracy is achieved with machine-learning methods using time series data.…”
Section: Methodsmentioning
confidence: 99%
“…Further, a study by Allcott and Gentzkow (2017) reported that 20% of the respondents recalled seeing fake news stories before the election campaign of 2016. However, Cantini et al (2022) discussed how the existence of social bots appears legitimate to social media users. These social bots were too effective in manipulating information and could work to influence public opinion.…”
Section: Information Dissemination Channels: Tool For Dispersing Misi...mentioning
confidence: 99%